Le texte littéraire : de la formation linguistique à l’expression de soi en passant par l’émerveillement - Puchovská, Zuzana (Neofilolog, 2022)
This article focuses on the use of literary text in a university context, within a curriculum that prepares future translators and interpreters. The author proposes to reflect on the role of language-dominant literary reading where the literary text can be approached as a linguistic object, an object of wonder and of self-expression. The first two roles are demonstrated in chapter 17 of the novel L’embrasure (2010) by the French-Swiss author D. Loup. The last role, self-expression, is the subject of the analysis of two collections of texts Et, si on faisait un livre ... (2019) and Amoureux des mots (2020), a joint writing project by the author and her students.